2018
DOI: 10.3389/fmicb.2018.01049
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of Aspergillus flavus on Peanut Kernels Using Streptomyces yanglinensis 3-10

Abstract: The bacterium, Streptomyces yanglinensis 3-10, shows promise in the control of many phytopathogenic fungi. In this study, S. yanglinensis and its antifungal substances, culture filtrate (CF3-10) and crude extracts (CE3-10), were evaluated for their activity in reducing growth and aflatoxin AFB1 production by Aspergillus flavus, both in vitro and in vivo on peanut kernels. The results showed that in dual culture conditions, S. yanglinensis reduced the mycelial growth of A. flavus about 41% as compared to contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 47 publications
(62 reference statements)
4
38
0
Order By: Relevance
“…Streptomyces spp. are well known as producers of hydrolytic enzymes and antifungal metabolites with inhibitory effects against many plant pathogenic fungi including Aspergillus species (Mander et al, 2016;Shakeel et al, 2018). Use of the VOCs from Streptomyces for control of Aspergillus contamination in peanut kernels has not been reported so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Streptomyces spp. are well known as producers of hydrolytic enzymes and antifungal metabolites with inhibitory effects against many plant pathogenic fungi including Aspergillus species (Mander et al, 2016;Shakeel et al, 2018). Use of the VOCs from Streptomyces for control of Aspergillus contamination in peanut kernels has not been reported so far.…”
Section: Discussionmentioning
confidence: 99%
“…are soil dwelling bacteria, they can grow and produce versatile secondary metabolites in soil. S. yanglinensis 3-10 was proved to produce antifungal metabolites which showed inhibitory effects on A. flavus growth and aflatoxin production and other plant pathogenic fungi (Lyu et al, 2017;Shakeel et al, 2018). It is an acidophilic species with high adaptation ability in acidic soils in southern China.…”
Section: Discussionmentioning
confidence: 99%
“…Several other Streptomyces species (Table 1) have been evaluated as bioactive agents providing an antagonistic activity against aflatoxigenic isolates. Shakeel et al [28] demonstrated that culture filtrates and crude extracts of S. yanglinensis could completely inhibit mycelial growth of A. flavus. Studies demonstrated that S. anulatus [29], S. alboflavus [30], and S. roseolus [31] also exerted an effective antifungal activity toward aflatoxigenic strains and other common agricultural crops pathogens.…”
Section: Streptomyces Sppmentioning
confidence: 99%
“…Streptomyces spp., known to produce over 7500 bioactive compounds including anticancer agents, vitamins, and antibiotic compounds, have a better tolerance to water stress [28]. They usually do not secrete toxic residues that may contaminate environments because of their natural origin.…”
Section: Micromolecular Organics Organic Acids and Enzymes Producedmentioning
confidence: 99%
“…Bacteria and non-toxigenic fungi were commonly used for Aspergillus flavus biocontrol and aflatoxin degradation. Streptomyces yanglinensis 3-10 ( Shakeel et al 2018) and Bacillus subtilis UTBSP1 (Farzaneh et al 2016) showed promising activity to control Aspergillus flavus in peanut kernel and pistachio nut. Non-toxigenic Aspergillus flavus (Ehrlich 2014) and Rhizopus stolonifer (Iqbal et al 2014) as mycelium or extract inhibited Aspergillus flavus growth.…”
Section: Introductionmentioning
confidence: 99%